'Daddy's Lil Monster': Suicide Squad, third-wave feminism and the pornification and queering of Harley Quinn. Issue 2 (1st October 2019) - Geczy, Adam; Karaminas, Vicki
Harley Quinn as she is represented in the film Suicide Squad directed by Ayers (2016) marks a dramatic and provocative departure from the manner in which she was originally cast in the DC Comics Batman: The Animated Series (1992) and Mad Love (1994). Depicted as an anti-hero in a dysfunctional relationship with The Joker, she is now transformed into a deviant and defiant super-villain in the film. Gone is her harlequin costume to be replaced with fishnets, blue and red velvet hot pants with red brassiere and high-top Adidas sneakers with heels. Although Quinn has been represented as heterosexual and stereotypically feminine there has always been a queer subtext operating. This article will examine the pornification and queering of Harley Quinn, through dress codes and appearance. It will argue that visual signifiers of femininity challenge notions of gender and sexuality and fold heterosexuality back upon its historical imperatives and conventions.